2009
DOI: 10.3168/jds.2008-1531
|View full text |Cite
|
Sign up to set email alerts
|

Hot topic: Changes in angiotensin-converting enzyme inhibition and concentrations of the tripeptides Val-Pro-Pro and Ile-Pro-Pro during ripening of different Swiss cheese varieties

Abstract: The angiotensin-converting enzyme (ACE) inhibitory activity and the concentration of the 2 ACE-inhibiting tripeptides Val-Pro-Pro (VPP) and Ile-Pro-Pro (IPP) were studied during cheese ripening in 7 Swiss cheese varieties. The semi-hard cheeses Tilsiter, Appenzeller 1/4 fat, Tête de Moine, and Vacherin fribourgeois and the extra-hard and hard cheeses Berner Hobelkäse, Le Gruyère, and Emmentaler were investigated. Three loaves of each variety manufactured in different cheese factories were purchased at the begi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 32 publications
1
35
0
2
Order By: Relevance
“…Further, 10 different Swiss cheese types were shown to contain the two antihypertensive peptides VPP and IPP in varying concentrations (Bütikofer et al, 2008;Meyer, Butikofer, Waither, Wechsler, & Sieber, 2009). Another study that analysed 13 commercial cheeses showed that both vintage and mature Cheddar cheese contains antihypertensive peptides as well as immunomodulatory and opioid peptides (Dionysius et al, 2000).…”
Section: Antihypertensive Activitymentioning
confidence: 95%
“…Further, 10 different Swiss cheese types were shown to contain the two antihypertensive peptides VPP and IPP in varying concentrations (Bütikofer et al, 2008;Meyer, Butikofer, Waither, Wechsler, & Sieber, 2009). Another study that analysed 13 commercial cheeses showed that both vintage and mature Cheddar cheese contains antihypertensive peptides as well as immunomodulatory and opioid peptides (Dionysius et al, 2000).…”
Section: Antihypertensive Activitymentioning
confidence: 95%
“…Van Platerink et al (2006) were also able to separate IPP and LPP (non-derivatised) but only in standard solutions or human plasma (0.05 ng mL À1 ) and, with hardly base line separation (11-23% overlapping areas, respectively). Another quantification method without pre-column derivatisation was published for VPP and IPP (Bütikofer, Meyer, Sieber, Walther, & Wechsler, 2008;Meyer, Bütikofer, Walther, Wechsler, & Sieber, 2009). The two authors quantified the bioactive peptides after LC separation using a sophisticated MS 3 analysis.…”
Section: Quantification Of Small Dabsylated Peptides In Fermented Milmentioning
confidence: 99%
“…Both tripeptides are also present in a commercial milk product called Evolus Ò , after fermentation of the milk with L. helveticus LBK-16H (Seppo, Kerojoki, Suomalainen, & Korpela, 2002). ACE inhibitory peptides have been isolated from a variety of other fermented products including cheese, fermented milk and yoghurt (Bütikofer, Meyer, Sieber, Walther, & Wechsler, 2008;Meyer, Bütikofer, Walther, Wechsler, & Sieber, 2009;Nakamura et al, 1995;Pihlanto, Virtanen, & Korhonen, 2010;Papadimitriou et al, 2007). Usually, the ACE inhibitory peptides are generated during the hydrolysis of milk proteins by lactic acid bacterial cell-bound proteinases (FitzGerald & Murray, 2006), or digestive enzymes (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, peptides from casein, Tyr-Pro-Phe-Pro-Gly-Pro-Ile-Pro-Asn (β-cn, f(60-68)); and Met-Pro-Phe-Pro-Lys-Tyr-Pro-Val-Gln-Pro-Phe (β-cn, f(109-119)) from Gouda [29] and Tyr-Gln-Glu-Val-Leu-Gly-Pro-Val-Arg-Gly-Pro-Phe-Pro-Ile-Ile-Val (-cn, f(193-209)) from Cheddar [30] have been identified. Antihypertensive peptides Val-Pro-Pro (VPP) (β-cn, f (84)(85)(86)) and Ile-Pro-Pro (IPP) (β-cn, f(74-76) and κ-cn, f(108-110)), have also been identified and quantified in different cheese varieties [31][32][33]. In some varieties physiologically relevant amounts was observed, however, a large variation exists between samples of the same cheese variety, as well as between different varieties.…”
Section: Peptides In Cheesementioning
confidence: 99%